Fingerprint template protection schemes: A literature review - Siswanto, Apri; Katuk, Norliza; Ku Mahamud, Ku Ruhana (JATIT, 2018)
The fingerprint is the most widely used technology for identification or authentication systems, which can be known as fingerprint authentication systems (FAS).In addition to providing security, the fingerprint is also easy to use, very reliable and has a high accuracy for identity recognition. FAS is still exposed to security attacks because fingerprint information is unencrypted.Therefore, fingerprint information requires protection known as fingerprint template protection (FTP).This paper aims to provide an organized literature on FTP.Three research questions were formulated to guide the literature analysis.First, this analysis focuses on the types of FTP schemes; second, the metrics used for evaluating the FTP schemes; and finally, the common datasets used for evaluating the FTP schemes. The latest information and references are analysed and classified based on FTP methods and publication year to obtain information related to the development and application of FTP.This study mainly surveyed 62 documents reported on FTP schemes between the year 2000 and 2017.The results of this survey can be a source of reference for other researchers in finding literature relevant to the FTP.